2022
DOI: 10.3390/ijms23105580
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Two Human RNA-seq Datasets to Determine Periodontitis Diagnostic Biomarkers and Drug Target Candidates

Abstract: Periodontitis is a chronic inflammatory oral disease that affects approximately 42% of adults 30 years of age or older in the United States. In response to microbial dysbiosis within the periodontal pockets surrounding teeth, the host immune system generates an inflammatory environment in which soft tissue and alveolar bone destruction occur. The objective of this study was to identify diagnostic biomarkers and the mechanistic drivers of inflammation in periodontitis to identify drugs that may be repurposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…Among the validated upregulated genes, CSF2RB was increased 100-fold in both periodontitis and peri-implantitis gingival tissues compared with the healthy state. CSF2RB, also known to increase expression in other periodontitis studies, is a gene that belongs to the "cytokine-cytokine receptor interaction" identified by KEGG pathway analysis, 34,35 which is known to participate in various signaling pathways, such as IL-3, IL-5, and granulocyte-macrophage colony-stimulating factor/CSF2 pathways. 36 Including CSF3 and MS4A1, which have previously been revealed as potential diagnostic markers for periodontitis, 34 many immune response genes, such as C3, CD79A, SELP, and IGHG2, were also confirmed to have increased expression in periodontitis and peri-implantitis, suggesting an active immune response during disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Among the validated upregulated genes, CSF2RB was increased 100-fold in both periodontitis and peri-implantitis gingival tissues compared with the healthy state. CSF2RB, also known to increase expression in other periodontitis studies, is a gene that belongs to the "cytokine-cytokine receptor interaction" identified by KEGG pathway analysis, 34,35 which is known to participate in various signaling pathways, such as IL-3, IL-5, and granulocyte-macrophage colony-stimulating factor/CSF2 pathways. 36 Including CSF3 and MS4A1, which have previously been revealed as potential diagnostic markers for periodontitis, 34 many immune response genes, such as C3, CD79A, SELP, and IGHG2, were also confirmed to have increased expression in periodontitis and peri-implantitis, suggesting an active immune response during disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, the Salmon read counts for each sample were combined into a tabular format and labeled as "resistant" or "sensitive" to treatment with Letrozole. This table was then used as input to the XGboost algorithm [39], which uses a tree-based method to train a model from 80% of the dataset and then quantifies its performance using the remaining 20% of the data [40,41], which minimizes model overfit. For the initial analysis, the gain metric was calculated from the read counts for all detected genes across all samples.…”
Section: Target and Biomarker Predictionmentioning
confidence: 99%
“…Given the gain metrics from the whole transcriptome, the number of genes/features being evaluated was reduced to the best two biomarkers from the original analysis since this is a number that is easily accommodated by qRT-PCR (or similar) molecular methods. This approach has been successfully applied previously with acceptable performance and accuracy [40,41,123]. The XGboost algorithm was selected since prior work has shown that tree-based classifiers are faster and more accurate than other machine learning-based methods such as support vector machine, neural networks, and Bayesian approaches [126].…”
Section: Target and Biomarker Predictionmentioning
confidence: 99%
“…Thus, further investigation on how treatment of oral inflammation impacts other inflammatory diseases can provide novel approaches to treating conditions such as Crohn's disease, cardiovascular disease, and Alzheimer's disease (Figure 2). Recently, our group performed a meta-analysis on publicly available RNAseq data to identify inflammatory mediators of periodontitis that contribute to local and systemic inflammation and potential drugs that can be repurposed to reduce inflammation (82). By performing analysis of differentially expressed genes and pathways, we determined that FDA-approved drugs that target IL-6 receptor, RANKL, and IFNα/ β receptor were among our top candidates to reduce chronic inflammation during periodontitis.…”
Section: The Oral Microbiota Affects Inflammatory Diseasesmentioning
confidence: 99%